A Systematic Review of the Effectiveness of Interventions to Improve Handwriting and Spelling in Children with Specific Learning Disabilities. Issue 4 (2nd October 2021) - Bray, Laura; Skubik-Peplaski, Camille; Ackerman, Kera B.
ABSTRACT: Handwriting and spelling deficits are common struggles experienced by children with specific learning disabilities (SLD), but there is little evidence on interventions that target these areas for children with SLD. To systematically review the research investigating the effectiveness of handwriting and spelling interventions for children with SLD. A systematic review was conducted that included studies focusing on handwriting and/or spelling interventions for children with SLD. A Black and Downs checklist was completed for each included article to evaluate validity and reliability. Effect sizes were calculated of results for a unitless comparison. Eleven studies met the inclusion criteria: six examined handwriting exclusively, three spelling, and two combined spelling and handwriting. The interventions were grouped into categories of tablet-based, sensorimotor, and/or self-management interventions. Themes of occupation-as-ends versus occupation-as-means were also noted. Those interventions that promoted self-management and used occupation-as-means were found to be most effective. Utilizing the handwriting and spelling within treatment as well as encouraging a child's autonomy and participation are valuable strategies for occupational therapist to use in improving literacy outcomes for children with SLD.